2001
DOI: 10.1046/j.1464-5491.2001.00509.x
|View full text |Cite
|
Sign up to set email alerts
|

Contraindications to metformin therapy in patients with Type 2 diabetes—a population‐based study of adherence to prescribing guidelines

Abstract: This population-based study shows that 24.5% of patients prescribed metformin have contraindications to its use. Development of contraindications rarely results in discontinuation of metformin therapy. Despite this, lactic acidosis remains rare. Diabet. Med. 18, 483-488 (2001)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
136
1
14

Year Published

2002
2002
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 189 publications
(156 citation statements)
references
References 19 publications
5
136
1
14
Order By: Relevance
“…Indeed, a population-based study shows that almost a quarter of patients prescribed metformin have contraindications to its use. Furthermore, development of contraindications rarely results in discontinuation of metformin therapy [16]. These data have been confirmed in several other studies in various countries [17,18].…”
Section: Introductionsupporting
confidence: 69%
See 2 more Smart Citations
“…Indeed, a population-based study shows that almost a quarter of patients prescribed metformin have contraindications to its use. Furthermore, development of contraindications rarely results in discontinuation of metformin therapy [16]. These data have been confirmed in several other studies in various countries [17,18].…”
Section: Introductionsupporting
confidence: 69%
“…In contrast to what has been reported for other glucose-lowering agents, especially the new incretin-based therapies, no specific trials have been performed assessing the benefit-risk balance of metformin use in patients with moderate or severe RI [51]. In the various series reporting real-life data, patients receiving metformin despite the presence of RI as official contraindication are not rare, apparently without any harm [16][17][18]. In the fourth National Health and Nutrition Examination Survey (NHANES IV), the proportion of patients using metformin progressively decreases according to the severity of RI, from 45.6 % at stage 1 to 23.8 at stage 3 and 0 % at stages 4 and 5 [52].…”
Section: Metformin In Patients With Renal Insufficiencymentioning
confidence: 92%
See 1 more Smart Citation
“…Moreover, both retrospective population-based studies [12] and studies in selected cohorts [10,11,13,14,35,36] showed that the currently proclaimed contraindications and precautions for metformin therapy are frequently disregarded (Table 2). Interestingly, among the ∼2,500 patients followed in these studies only one case of lactic acidosis was reported, and even this one case could not be causally attributed to metformin since it was associated with intercurrent myocardial infarction and renal failure [12].…”
Section: Disregard Of Metformin Contraindications and Incidence Of Lamentioning
confidence: 99%
“…The first is that some patients do not tolerate it well, and the second is that traditional contraindications limit its use [5][6][7][8][9]. Although such contraindications are frequently overlooked in clinical practice, an increased incidence of serious side-effectsparticularly lactic acidosis-has not been observed [10][11][12][13][14]. This raises the question whether the contraindications, as currently outlined, deprive many patients with type 2 diabetes of the benefits of metformin.…”
Section: Introductionmentioning
confidence: 99%